Sistem Non-Invasif Untuk Pengukuran Kadar Glukosa, Oksigen, dan Detak Jantung Berbasis LED Merah dan Infrared Dekat - bakir, ahmad; Mardianto, Eko; Riyanto, Agus (Jurnal ELIT, 2024)
This research aims to develop a non-invasive health monitoring system capable of measuring glucose levels, oxygen saturation, and heart rate using near-infrared (NIR) technology and a red LED, without the need for needle pricks. This system is designed to address the drawbacks of invasive methods that require blood samples, which often cause discomfort and risk of infection, especially for diabetic patients. The research methodology includes the development and testing of a device based on the MAX30102 sensor, utilizing an infrared wavelength of 900 nm and a red LED at 670 nm, along with the mega328P microcontroller for data processing. The research results indicate that this technology has significant potential to improve the quality of life for diabetic patients by offering a convenient, safe, and practical health monitoring solution. Measurement results show consistency with comparative devices, indicating the relevance and accuracy of this technology. This research opens up opportunities for further advancements in non-invasive health monitoring technology.